2017
DOI: 10.5433/1679-0359.2017v38n4suplp2595
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and virulence genes in Streptococcus uberis strains isolated from bovine mastitis

Abstract: ResumoA mastite é uma das doenças infecciosas mais onerosas em bovinos leiteiros em todos os continentes. Trata-se de uma doença de cunho multifatoral causada por diferentes microrganismos, incluindo vírus, leveduras, algas, parasitas e várias espécies de bactérias. Entre as bactérias, Streptococcus uberis destacase como um importante agente ambiental, responsável por uma grande variedade de infecções clínicas e subclínicas da glândula mamária, especialmente em sistemas de produção intensivos. Apesar da cresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Indeed, the heterogeneity of PFGE patterns in one hand and the close relationship among other strains on the other hand (Fig. 1) confirm the epidemiological role of S. uberis in mastitis induction via cow-to-cow transmission in agreement with previous reports [1], [6]. However, this suggestion counteracts the widespread believe that S. uberis infections usually result from environmental infections [2], [8], [12], [17].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Indeed, the heterogeneity of PFGE patterns in one hand and the close relationship among other strains on the other hand (Fig. 1) confirm the epidemiological role of S. uberis in mastitis induction via cow-to-cow transmission in agreement with previous reports [1], [6]. However, this suggestion counteracts the widespread believe that S. uberis infections usually result from environmental infections [2], [8], [12], [17].…”
Section: Discussionsupporting
confidence: 88%
“…In the present work, all involved field isolates (n = 47) were identified phenotypically as well as genotypically as S. uberis . For the typing of isolates at their strain level, PFGE was used due to its high discriminatory index in distinguishing field strains of S. uberis as recommended previously [1], [19] This was confirmed by the delivered data in the present work where a weak relationship among the detected genotypic profiles could be noticed. The data showed that S. uberis isolated from different herds belonged to different genotypic groups with various sets of PFGE patterns.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…skC is another gene which codes for a plasminogen activator. A study by Loures in Brazil has shown that this gene, along with pauA, is highly conserved between different strains of S. uberis [57].…”
Section: Pathogenesis and Virulence Factorsmentioning
confidence: 99%
“…Consistent with its environmental origin, many authors have reported a high level of Strep. uberis diversity within investigated herds (Douglas et al, 2000;Khan et al, 2003;McDougall et al, 2004;Tomita et al, 2008;Haenni et al, 2010;Lasagno et al, 2011;Lundberg et al, 2014;Reinoso et al, 2015;Loures et al, 2017). Some Strep.…”
Section: Introductionmentioning
confidence: 99%